2015
DOI: 10.3177/jnsv.61.113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Vitamin E Supplementation on Liver Oxidative Damage in Rats with Water-Immersion Restraint Stress

Abstract: Water-immersion restraint stress (WIRS), which is characterized with both psychological stress and physical stress, is widely used to induce reproducible stress ulcers in experimental animals (1). Reactive oxygen species (ROS) and nitric oxide ( • NO) generation, lipid peroxidation, and neutrophil infiltration in the gastric mucosal tissue play a critical role in the pathogenesis of WIRS-induced gastric mucosal lesions (2-5). Iwai et al. (6) have reported that, in rats with 6 h of WIRS, the level of liver lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…In opposite, Rodríguez-Gutiérrez et al [29] and Ohta et al [45] showed the ability of vitamin E to inhibit lipid peroxidation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In opposite, Rodríguez-Gutiérrez et al [29] and Ohta et al [45] showed the ability of vitamin E to inhibit lipid peroxidation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation of TAC and reduction of MDA are expected due to the antioxidant activity of both vitamin E and turmeric. Vitamin E was reported to stabilize mitochondrial function and protect the liver against oxidative damage with consequent anti-inflammatory activity thereby could prevent progression of fatty liver to steatohepatitis 54,61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Kinoshita et al, ; Yano et al, ), a whole blood sample was withdrawn into a heparinized syringe from the abdominal inferior vena cava of each mouse under lethal anaesthesia with pentobarbital. The anaesthesia itself reportedly does not influence host immune cells (Isobe, Okajima, Harada, Liu, & Okabe, ; Ohta et al, ). The whole blood sample was mixed with dextran in a 4:1 volume ratio, then laid flat for 30 min.…”
Section: Methodsmentioning
confidence: 99%